The Influence of Work Discipline, and Leadership on Employee Performance Through Oversight at the Customs and Excise Service Office for Middle Type Customs Juanda - Ardiansyah (Yayasan Gema Bina Nusantara, 2023)
This study aims to analyze the influence of work discipline and leadership on employee performance through supervision at the Customs and Excise Service Office of the Juanda Customs Type. Using quantitative methods and measuring instruments SPSS version 26. Respondents used were 134 respondents. The results of this study are the influence of Work Discipline and Leadership on Employee Performance through Supervision at the Customs and Excise Supervision and Service Office of the Juanda Customs Middle Type.